Фотонно кристалічний хвилевід з гіротропними елементами - Новицький, В. В.; Демиденко, Є. Є. (ХНУРЕ, 2024)
This study investigates the influence of an external magnetic field on the dispersion properties and operational features of photonic-crystal waveguides composed of gyrotropic elements. Numerical simulations using the MEEP package for waveguide characterization and MIT Photonic Bands for analysis of the dispersion characteristics of the infinite photonic crystal reveal insights into the behavior of these structures under magnetic influence, elucidating fundamental principles for potential applications in photonics.
Keywords: фотонно-кристалічний хвилевід; гіротропний елемент